Jewish childhood in the Roman world - Sivan, Hagith, 1949- (Cambridge : Cambridge University Press, 2018)
This is the first full treatment of Jewish childhood in the Roman world. It follows minors into the spaces where they lived, learned, played, slept, and died and examines the actions and interaction of children with other children, with close-kin adults, and with strangers, both inside and outside the home. A wide range of sources are used, from the rabbinic rules to the surviving painted representations of children from synagogues, and due attention is paid to broader theoretical issues and approaches. Hagith Sivan concludes with four beautifully reconstructed'autobiographies' of specific children, from a boy living and dying in a desert cave during the Bar-Kokhba revolt to an Alexandrian girl forced to leave her home and wander through the Mediterranean in search of a respite from persecution. The book tackles the major questions of the relationship between Jewish childhood and Jewish identity which remain important to this day.
Preface: What is the study of Jewish childhood? -- Part I: Theories -- Chapter 1. Theorizing the Jewish child -- Chapter 2. Vagaries of childhood: from cradles to graves -- Chapter 3. Bringing up boys -- Chapter 4. Daughters: delight or dissension? -- Chapter 5. Burdened at birth: the misbegotten and the malformed -- Part II: Children in the synagogue -- Chapter 6. Visualizing the Bible -- Chapter 7. The painted children of the Dura Europos Synagogue -- Part III: Autobiographies -- Chapter 8. Sukkot in a cave (CE 135) -- Chapter 9. Passover in the Port of Rome (Ostia c. CE 175) -- Chapter 10. Sabbath in Tiberias (c. 300) -- Chapter 11. The birth of a wandering Jewess (C. ce 415-435) -- Conclusion: The invention of rabbinic childhood.
Title from publisher's bibliographic system (viewed on 20 Jun 2018).
Keywords: Jewish Children -- Rome -- History -- To 510 B.C.; Jewish Children -- Rome -- Social conditions -- History -- To 510 B.C.; Rome -- History -- To 510 B.C.